2002
DOI: 10.1046/j.1365-2842.2002.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic influence of food consistency on the masticatory motion

Abstract: The masticatory cycle is a complex process and it depends on many factors. In our study we wanted to prove to what extent various types of food consistency influence the masticatory motions, especially the extent of forward, downward and lateral motions of the mandible. Nineteen study subjects aged from 20 to 37 years and with intact teeth rows were asked to chew three types of food of various consistency (banana, bread and carrot). The motions of the mandible were recorded by stereo-photo-grammetric system. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The closing angle and width of the chewing loop were found to be significantly correlated with the toughness and modulus of elasticity, which were two mechanical properties of the food, whereas the vertical movement was not correlated [45]. In addition, it was reported that, in vivo, the lateral chewing motion was dependent on the consistency of the food, although differences between subjects were observed due to the retro control by mechanoreceptors [46]. A greater consistency of foods resulted in a larger lateral chewing motion of the lower jaw.…”
Section: Discussionmentioning
confidence: 99%
“…The closing angle and width of the chewing loop were found to be significantly correlated with the toughness and modulus of elasticity, which were two mechanical properties of the food, whereas the vertical movement was not correlated [45]. In addition, it was reported that, in vivo, the lateral chewing motion was dependent on the consistency of the food, although differences between subjects were observed due to the retro control by mechanoreceptors [46]. A greater consistency of foods resulted in a larger lateral chewing motion of the lower jaw.…”
Section: Discussionmentioning
confidence: 99%
“…Uma das primeiras preocupações com a avaliação da função mastigatória deve ser em relação ao tipo e à quantidade do alimento a ser oferecido ao paciente durante a avaliação clínica, para que se tenham parâmetros normativos e de comparação entre os diferentes casos. Sabe-se que o tipo de alimento modifica a função mastigatória, em relação ao tempo dos ciclos e ato mastigatório, número, frequência e ritmo dos ciclos mastigatórios e movimentos mandibulares 23,[32][33][34] .…”
Section: Discussionunclassified
“…Previous kinematic studies on mastication analyzed either the path of a single mandibular point, for instance the incisal or gnathion (Jemt et al, 1979;Ha¨ggman-Henrikson et al, 1998;Filipic and Keros, 2002;Haggman-Henrikson and Eriksson, 2004), or of several mandibular points simultaneously (Gibbs et al, 1971;Gibbs et al, 1981;Gibbs et al, 1982;Miyawaki et al, 2000;Miyawaki et al, 2001;Nakajima et al, 2001), or of a condylar point, such as the kinematic center (Naeije and Hofman, 2003). One of the limitations of the single point analysis is that it is very sensitive to the choice of its coordinates.…”
Section: Masticationmentioning
confidence: 99%